2015
DOI: 10.1530/erp-15-0003
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional echocardiography of congenital abnormalities of the left atrioventricular valve

Abstract: Congenital abnormalities of the left atrioventricular (AV) valve are a significant diagnostic challenge. Traditionally, reliance has been placed on two-dimensional echocardiographic (2DE) imaging to guide recognition of the specific morphological features. Real-time 3DE can provide unique views of the left AV valve with the potential to improve understanding of valve morphology and function to facilitate surgical planning. This review illustrates the features of congenital abnormalities of the left AV valve as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 45 publications
0
21
0
Order By: Relevance
“…Their publication shows the importance of three-dimensional imaging to demonstrate the extent of the papillary muscle and to describe the subvalvar apparatus in situations such as the absence of chordae and loss of interchordal spaces that cannot be projected on two-dimensional echocardiographic images. 16 Another recent study by Rim et al on parachute mitral valve demonstrated a strong correlation between the reduction of mitral orifice size and the degree of asymmetry of the papillary muscle location. Moreover, there was a considerable reduction in leaflet coaptation and abnormal leaflet deformation corresponding to the anomalous location of the papillary muscle tips; 17 three-dimensional echocardiography therefore has a complementary role in the assessment of patients with borderline or hypoplastic left ventricles, and this is the patients of ongoing clinical research.…”
Section: Discussionmentioning
confidence: 93%
“…Their publication shows the importance of three-dimensional imaging to demonstrate the extent of the papillary muscle and to describe the subvalvar apparatus in situations such as the absence of chordae and loss of interchordal spaces that cannot be projected on two-dimensional echocardiographic images. 16 Another recent study by Rim et al on parachute mitral valve demonstrated a strong correlation between the reduction of mitral orifice size and the degree of asymmetry of the papillary muscle location. Moreover, there was a considerable reduction in leaflet coaptation and abnormal leaflet deformation corresponding to the anomalous location of the papillary muscle tips; 17 three-dimensional echocardiography therefore has a complementary role in the assessment of patients with borderline or hypoplastic left ventricles, and this is the patients of ongoing clinical research.…”
Section: Discussionmentioning
confidence: 93%
“…proximal isovelocity surface area or vena contracta) have been used. In addition, few studies addressed technical issues 2,3,43,44 related to settings on the echocardiographic systems (such as image and colour gain as well as the Nyquist limit for Doppler interrogation).…”
Section: Methodological Limitationsmentioning
confidence: 99%
“…Significant anomalies of the mitral valve account for 0.4% of CHDs; however, minor anomalies of the mitral valve may be detected in up to 4% of school-aged children. [8][9][10][11][12][13][14][15][16][17][18][19][43][44][45][46][47][48][49][50] Echocardiographic evaluation of mitral valve diseases in the paediatric age group requires a careful sequential analysis of multiple valvular elements (annulus, leaflets, chordae, inter-chordal space, and papillary muscles) and knowledge of anatomical variants and of associated CHD. Beside the anatomical analysis, a quantitative and semi-quantitative evaluation of disease severity (i.e.…”
mentioning
confidence: 99%
“…In the presence of single papillary muscle, the valve is described as true parachute MV and when two muscles are detected as parachute‐like MV. Isolated form of PLMV accounts for less than 1% and documented number of adults is sparse …”
Section: Case Descriptionmentioning
confidence: 99%
“…Isolated form of PLMV accounts for less than 1% and documented number of adults is sparse. [1][2][3][4] Simultaneous visualization of this complex anatomy and function is markedly enhanced using focused high-resolution 3D acquisition of the valve, allowing for improved perception of unusual valve anatomy, multiplanar image reformatting, and unbiased quantification, which is important for individualized treatment choices.…”
mentioning
confidence: 99%